Analisis Pemberian ASI Eksklusif di Posyandu Wilayah Kerja Puskesmas Bukitsangkal Palembang Tahun 2024 2024 - Lastrini, Anggun; Wahyudi, Arie; Zaman, Chairil; Eddy Sapada, Ibrahim (Public Health Department, Faculty of Health Science University Muhammadiyah Bengkulu, 2024)
Background: Exclusive breast milk is breast milk given to babies from birth for six months, without adding and/or replacing it with other foods or drinks (except medicines, vitamins and minerals). This study aims to determine the analysis of exclusive breastfeeding in Posyandu in the Bukitsangkal Palembang Public Health Center working area in 2024. Method: This research design used cross sectional, where the population in this study was 753 respondents, with a sample of 89 respondents under toddlers aged 6-23 months. The sampling method in the research was proportional random sampling. This research was carried out from April 22 to June 1, 2024. Data was collected and retrieved using questionnaires and observations. Results: Results of statistical test analysis using the Chi-Square statistical test and logistic regression where the results show that there is a significant relationship (p value < 0.05) for the variables age (p value 0.009), occupation (p value 0.002), education (p value 0.019), income (p value 0.002), knowledge (p value 0.026), IMD (p value 0.030), family support (p value 0.000), parity (p value 0.021) and support from health workers (p value 0.013). From the results of multivariate statistical tests, it was found that the dominant factor in exclusive breastfeeding was family support (p= 0.004; OR= 10.020). Suggestion: It is hoped that health workers will pay attention to the achievements of exclusive breastfeeding and provide counseling or education to mothers regarding the benefits of exclusive breastfeeding for 6 months without any additional food so that it is hoped that they can increase the target of exclusive breastfeeding. Keywords: Breastfeeding, Toddlers, Giving, Posyandu